Professional identity of language teacher trainees during practicum: A metaphor analysis - Burcu Turhan (Literacy Trek, 2022)
Teachers may face dilemmas when they realize certain discrepancies between theory and practice throughout their career. Especially for teacher trainees, such dilemmatic spaces may be beneficial in uncovering multiple identities developing and being shaped especially during practicum. More specifically, the most frequent discrepancy could be between the desire to explore one's own teacher identity and to please mentors and supervisors. Therefore, teacher training programs should provide spaces for teacher trainees to reflect and analyze those dilemmas so that they could develop their teacher professional identity (TPI) in an unproblematic and smooth manner. To this end, this study involved twelve senior English teacher trainees into a five-week process when they expressed their growing professional identities through metaphorical discourse within the scope of Teaching Practice I course. The thematic analyses of the elicited metaphors revealed vital hints about the TPI of language teacher trainees. Besides, the place and importance of metaphors for understanding TPI were discussed in the context of teacher education.